Investigating the self healing process on coated steel by SVET and EIS techniques. Issue 1 (2nd May 2012) - Neema, S.; Selvaraj, M.; Raguraman, J.; Ramu, S.
Abstract Microencapsule was incorporated into an interpenetrating polymer network and applied over steel surface. A scratch was made on the coated surface and its self healing ability was studied using scanning vibrating electrode technique (SVET) and electrochemical impedance spectroscopy (EIS). Results of SVET studies show that the current density increases in the initial stage. After 24 h, the current density decreases, which indicating the formation of passive polymer film due to the diffusion of core polymer present in the microcapsules through the holidays. Increase in the resistance (107 Ω/cm2) of the self healing coating was observed after 24 h in EIS studies confirming the formation of the passive film. The results of the studies are discussed in this article. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012